Kierkegaard, Mimesis, and Modernity A Study of Imitation, Existence, and Affect - Kaftanski, Wojciech (Taylor & Francis, 2021)
Philosophy, Kierkegaard, 19th century philosophy, history of philosophy, aesthetics, religion and philosophy